The bombers : the illustrated story of offensive strategy and tactics in the twentieth century - Cross, Robin, 1948- (New York : Macmillan, 1987)
Detailed and illustrated analyses of design breakthroughs and flaws, crucial operations and notable disasters is placed in the wider context of moral and practical arguments about the proper use of the bombing arm.
Includes bibliographical references (page 224) and index.
Keywords: Bombing, Aerial -- History; Bombers; History